2005
DOI: 10.1081/prg-200059836
|View full text |Cite
|
Sign up to set email alerts
|

MMP-2 Levels are Elevated in the Plasma of Women Who Subsequently Develop Preeclampsia

Abstract: At all three gestational time points an imbalance in the MMP-2:TIMP-1 ratio was found in patients who subsequently developed preeclampsia. We speculate that increased net MMP-2 activity may contribute to the endothelial dysfunction that is central to the pathophysiology of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
78
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 28 publications
11
78
1
3
Order By: Relevance
“…While MMP-2 genotypes and haplotypes are not linked with hypertensive disorders of pregnancy, MMP-2 genotypes and haplotypes are associated with significant alterations in plasma MMP-2 and TIMP-2 concentrations in preeclampsia. The increased MMP-2 concentrations in preeclampsia agree with results previously reported (Montagnana et al, 2009;Myers et al, 2005b;Narumiya et al, 2001). Although the increased TIMP-2 concentrations that we found in preeclampsia contrast with previous results (Montagnana et al, 2009), our findings align with similar findings reported in another cross-sectional study (Tayebjee et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While MMP-2 genotypes and haplotypes are not linked with hypertensive disorders of pregnancy, MMP-2 genotypes and haplotypes are associated with significant alterations in plasma MMP-2 and TIMP-2 concentrations in preeclampsia. The increased MMP-2 concentrations in preeclampsia agree with results previously reported (Montagnana et al, 2009;Myers et al, 2005b;Narumiya et al, 2001). Although the increased TIMP-2 concentrations that we found in preeclampsia contrast with previous results (Montagnana et al, 2009), our findings align with similar findings reported in another cross-sectional study (Tayebjee et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…Impaired MMP activity is involved in many clinical conditions affecting the cardiovascular system including hypertensive disorders of pregnancy (Montagnana et al, 2009;Myers et al, 2005b;Narumiya et al, 2001;Palei et al, 2008;Tayebjee et al, 2005). Specifically, MMP-2 may be involved in uteroplacental artery remodeling and control of cytotrophoblastic invasion (Isaka et al, 2003;Shimonovitz et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these factors might be contributing to poor migration and proliferation of the endothelial cells and poor development of new blood vessels. The observed high expression of MMP2 in maternal blood in preeclampsia is consistent with the documented high level of MMP2 in preeclamptic plasma (Myers et al 2005) and might have a role in regulating vascular tone, as highlighted by a recent study that suggested the role of MMP1 expression in vasoconstriction (Mousa et al 2012). Consistent with our results, high levels of TIMP1 and TIMP2 have been demonstrated in preeclamptic endothelial cells (Merchant et al 2004).…”
Section: Discussionsupporting
confidence: 80%
“…An imbalance in the MMP-2/TIMP-1 ratio has been found in women who develop preeclampsia. 44 Thus, up-regulation of Nodal and ALK7 may contribute to the pathogenesis of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%